Analysis of Factors Affecting Fatigue Level in Online Motorcycle Taxi Drivers in Denpasar City - Sahadewa, Anak Agung Gede Anandyaksa Waranggana; Apsari, Putu Indah Budi; Wijaya, Putu Austin Widyasari (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Ojek online is an online-based transportation that is currently popular. Along with the rise of this drivers, it causes an increase in the number of accidents that occur. Factors that cause fatigue consist of age, gender, workload, length of service, and duration of work. Fatigue is the most workload experienced by online motorcycle taxi drivers in Denpasar. The purpose of this research is to determine the factors that affect job fatigue in online motorcycle taxi drivers, such as age, gender, smoking habits, length of work, duration of work, and body mass index. This study is an observational study with a cross sectional design and used the Industrial Fatigue Research Committee questionnaire. The subjects of this study were online motorcycle taxi drivers in Bali, especially in Denpasar City, totaling 106 people selected based on the inclusion and exclusion criteria using purposive sampling technique. The majority of this subjects are male (51,2%), duration of work of >8 hours (69,1%), work for >2 years (61,5%), aged 37 years (66,1%), and obese (100%) experiencing job fatigue. The results of the analysis obtained smoking factors, work duration, length of work, age, and body mass index affect work fatigue in online motorcycle taxi drivers.